2008
DOI: 10.1590/s0104-56872008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do programa de remediação auditivo-visual computadorizado em escolares com dislexia

Abstract: Background: an audio-visual computerized remediation program in students with developmental dyslexia. Aim: to verify the efficacy of an audio-visual computerized remediation program in students with developmental dyslexia. The specific goals of this study involved the comparison of the linguisticcognitive performance of students with developmental dyslexia with that of students considered good readers; to compare the results obtained in pre and post-testing situations of students with dyslexia who were and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
(1 reference statement)
3
18
0
8
Order By: Relevance
“…As for processing J Soc Bras Fonoaudiol. 2011;23(1): [13][14][15][16][17][18][19][20] speed, there was statistically significant difference in pre-testing and post-testing between the scores obtained by G1 for rapid automatized naming of pictures and rapid automatized naming of digits with the reduction of naming time. Table 3 is the description of the mean, standard deviation and p-value of the performance of students in pre-testing and post-testing regarding visual processing skills of the CognitiveLinguistic Performance Test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for processing J Soc Bras Fonoaudiol. 2011;23(1): [13][14][15][16][17][18][19][20] speed, there was statistically significant difference in pre-testing and post-testing between the scores obtained by G1 for rapid automatized naming of pictures and rapid automatized naming of digits with the reduction of naming time. Table 3 is the description of the mean, standard deviation and p-value of the performance of students in pre-testing and post-testing regarding visual processing skills of the CognitiveLinguistic Performance Test.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are international and national studies which describe the use of remediation programs (12)(13)(14)(15) , there are few national studies on children with learning difficulties, highlighting the need for research to adjust or develop remediation programs for the specific treatment of cognitive-linguistic change in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a person presents normal intelligence, phonological disorder, failure in semantic, syntactic and pragmatic skills, presenting impaired narrative ability in the process of recounting stories, correctly fluency difficulty in decoding and spelling skills, in addition to changes in processing and auditory and visual information. 7,8 It was evidenced in the literature, familial recurrence for dislexia 9 . Studies show that dyslexia has a major familial incidence 10 , which is an important risk factor for diagnosis 11,12 .…”
Section: Methodsmentioning
confidence: 97%
“…It was also observed that this intervention provided longer time of attention at the activities by the students 19 . Subsequently, the effects of CAT in students with learning disabilities were researched, verifying that such audience presents delayed development of auditory skills, which prevents the correct assimilation of received auditory information 20 .…”
Section: Literature Reviewmentioning
confidence: 76%